The investigation of genetic etiology in familial cases with congenital hypothyroidism - Kardelen Al, Aslı Derya; Işık, Fatma Büşra; Karakılıç Özturan, Esin; Sözügüzel, Mavi Deniz; Öztürk, Ayşe Pınar; Poyrazoğlu, Şükran; Parlayan, Cüneyd; Cangül, Hakan; Baş, Firdevs; Darendeliler, Feyza (Karger, 2019)
Background: Congenital hypothyroidism(CH) is the most common neonatal endocrinological disorder in the world. Although most of the CH is sporadic, some genetic defects are responsible from the etiology. The aim of this study was to determine the genetic and etiological factors of CH. Methods: 49 patients(female;n=24), from 24 families were included in the study. The data, collected retrospectively, consisted of medical history, physical examination, clinical findings, thyroid hormone levels and etiological tests. Gene panel consisting of 19 genes(PAX8,NKX2-1,NKX2-5,FOXE1,TSHR,SLC5A5,SLC26A4,TG,TPO,DUOX2, DUOXA2,IYD,SLC26A7,DUOX1-ZNF607,SLC6A4,GLIS3,TSHB,THRA) that may cause CH was performed. Pathogenicity of the novel nonsynonymous mutations were analysed via in silico prediction programs. Results: Sixteen families had consanguineous marriages and 12 families had a history of hypothyroidism. Twenty patients were diagnosed with neonatal screening programme and 2 patients with hyperbilirubinemia, 5 patients were diagnosed during hospitalization in neonatal intensive care unit and 22 patients were diagnosed during the routine control. The mean age at presentation (mean±SD) was 1.3±2.1 years (median:0.2;range0.03-8.8). The mean TSH level at presentation was 152.3±207.9mIU/ml (median:51.8;range4.2-820), and the level of fT4 was 8.8±5.9 pmol/L(median:9.4;range0.04-19.7). All patients underwent ultrasonography and one patient had thyroid agenesis. Scintigraphy was performed to 23 patients and thyroid agenesis and thyroid hyperplasia were detected in two patients. Perchlorate discharge test was performed on 21 patients and two of them could not be evaluated due to errors in processing. Four patients had normal results, 9 patients had partial dyshormogenesis and 6 patients had complete dyshormogenesis. Genetic analysis revealed that four families with consanguineous marriages (4/24,16.7%) had mutations in 3 different genes. Two families were followed because of complete dyshormogenesis and two families were followed because of partial dyshormogenesis. Family I had a homozygous c.1349G>A(p.R450H) mutation in the TSHR gene. Second family had a homozygous c.1477G>A(p.G493S) mutation in the TPO gene. Third family had a homozygous missense p.R540X mutation in the TPO gene. Family IV had a homozygous novel c.280G>A(p.G94R) mutation in the SLC26A7 gene. Conclusion: In our study, the overall mutation rate was 16.7%. Genetic etiologies may differ in patients with dyshormonogenesis. A novel mutation was shown in the SLC26A7 gene in a family with partial dyshormogenesis. Genetic analysis can be used to clarify the etiology, to be informed about prognosis and to provide genetic counseling especially in familial cases. It has been suggested that a greater number of related genes should be screened for the recognition of genetic causes that may cause of CH.
Keywords: Congenital Hypothyroidism; Genetic; Etiology